2020
DOI: 10.2172/1648302
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrogen Generation in High Burnup Demonstration Dry Storage Cask

Abstract: This report provides a best-estimate evaluation of residual water content (post-dry out) in the High Burnup (HBU) LWR Spent Fuel Demonstration project TN-32 cask, and evaluates the radiolysis of the residual free water, and the physisorbed and chemisorbed waters on the surfaces of the fuel and cask internal contents. 1 The evaluation of radiolytic breakdown of those waters with gamma radiation causing the generation of hydrogen gas (H2) is made using available literature data and models. This evaluation is pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Key predictions in Ref. [d'Entremont et al, 2020] indicated that 1) short-term hydrogen generation would be dominated by radiolysis of water adsorbed to Zr-alloy surfaces due to energy transfer from the solid to the adsorbed water and 2) the amount of hydrogen generated by this mechanism would be heavily dependent on whether or not the surface-adsorbed water could be replenished by water vapor.…”
Section: Water Radiolysis and Hydrogen Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…Key predictions in Ref. [d'Entremont et al, 2020] indicated that 1) short-term hydrogen generation would be dominated by radiolysis of water adsorbed to Zr-alloy surfaces due to energy transfer from the solid to the adsorbed water and 2) the amount of hydrogen generated by this mechanism would be heavily dependent on whether or not the surface-adsorbed water could be replenished by water vapor.…”
Section: Water Radiolysis and Hydrogen Generationmentioning
confidence: 99%
“…In addition, surface water decomposed by radiolysis may be replenished by water vapor in the canister gas, providing a mechanism for accelerated radiolysis of the free water as well. The previous simplified analysis [d'Entremont et al, 2020] predicted that radiolysis of physisorbed water on the Zr-alloy components would dominate the short-term H2 generation due to these factors. Therefore, the yield associated with water radiolysis on the Zr surfaces (physisorbed water, with potential replenishment from water vapor) is the focus of the current testing.The lab-scale testing is conducted on non-radioactive surrogates, namely assemblies of zirconium coupons, irradiated inside a miniature steel canister ("mini-canister") designed to allow intermittent, insitu sampling of the canister gas during irradiation.…”
mentioning
confidence: 99%
See 2 more Smart Citations